Limitation Of Authority For The Government To Access Information For Tax Purposes In The Perspective Of Law And Human Rights - Munir, Ahmad; Djatmiati, Tatiek Sri; Aisyah, rr. Herini Siti (Indonesian Journal of Law and Society, 2024)
Regulation regarding access to financial information for tax purposes gives authority to the government delegated to the Directorate General of Taxes to obtain access to financial information from financial service institutions. This is considered contrary to the right to privacy and confidentiality, resulting in the need to limit government authority to protect taxpayers. This research answers taxpayers' doubts about government authority over access to financial information and gains taxpayers' confidence in the security and confidentiality of financial information. This research uses normative juridical methodology with a statutory and conceptual approach related to tax information disclosure. Legal protection for taxpayers must be implemented based on the rule of law by limiting the government's authority to access financial information for tax purposes. Changing permission to become a dispensation in regulations regarding access to financial information for tax purposes must provide justice for taxpayers so that there is no freedom from government authority. So, it would be unfair to treat compliant taxpayers like non-compliant taxpayers. Obedient taxpayers have carried out their obligations and are entitled to the right to privacy and confidentiality of their financial information. For this reason, it is necessary to limit the authority for the Directorate General of Taxes so as not to take arbitrary actions in accessing taxpayer financial information, as well as ensuring the confidentiality of financial information, so as to create fairness in the implementation of access to financial information for tax purposes.